Estimation of Vascular Cell Adhesion Molecule 1 (VCAM-1) Levels In Type 1 Diabetic Mellitus Patients - Akram Saterr, Ousamha; Hassan, Abeer J.; Adnan Rasheed, Qahtan (Bionatura, 2021)
High glucose levels in patients with diabetes are associated with increased plasma levels of soluble adhesion molecules. They could explain that the patients with diabetes mellitus will require the development of premature atherosclerosis related to hyperglycemia or hyperinsulinemia and that it not only affects vascular endothelium but also contributes to the development of microvascular complications. This study aimed to evaluate the serum concentration of VCAM-1 in type 1 diabetes mellitus patients with and without cardiovascular disease. Also, investigation the association of insulin levels, duration of diabetes, and HbA1C with VCAM-1. Include in this study a total of 60 types 1 diabetic patient. According to characteristic laboratory investigations and electrocardiogram (ECG), they were subdivided into two groups (G1) 30 T1DM patients without cardiovascular disease and (G2) 30 T1DM patients with cardiovascular disease in addition to 30 healthy subjects as a control group (G3). All subjects measured the levels of fasting blood glucose FBG, glycated hemoglobin HbA1c, and insulin levels, and VCAM-1 were also determined by ELISA technique. This study shows a highly significant difference in the average diabetic profile between G1 and G2 compared to the control group and found that VCAM-1 level was significantly higher among diabetic patients than the control group. Also, there was a significant negative correlation of VCAM-1 with the levels of FBG, HbA1c in diabetic patients G1 and G2. While insulin had a positive correlation in G1 but correlated negatively in G2